Measuring | V t d | at the LHC - Alvarez, Ezequiel; Da Rold, Leandro; Estevez, Mariel; Kamenik, Jernej F. (American Physical Society, 2018)
Fil: Alvarez, Ezequiel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de San Martín; Argentina